The chocolate raccoon rigmarole - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery, 2021)
"In this eighteenth mystery in the national bestselling Chocoholic series, a gang of crooks with a wicked sweet tooth wreaks havoc on the resort town of Warner Pier, and it's up to Lee Woodyard to rout the hungry rascals. A frantic late-night phone call from her right-hand woman, Dolly Jolly, brings Lee Woodyard to the scene of a break-in at the Warner Pier jewelry store next door to TenHuis Chocolade. To her shock, the suspect being held at gunpoint by police is Dolly's boyfriend, Mike Westerly, who was recently hired as a night watchman specifically to prevent break-ins. Dolly hopes Lee can help straighten out the crazy misunderstanding. Even crazier? The thieves took nothing of value from the jewelry store, only swiping some snacks. It's another in a series of break-ins by burglars the media has dubbed the Cookie Monsters. They've been hitting shops selling everything from sunglasses to shoes but stealing only sweets: lollipops, cookies, even chewing gum! It all seems pretty funny-until the discovery of a dead body. With her friends and community in danger, Lee must stop one very sour killer before someone else comes to a bitter end"--